Myodes rutilus ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
52. Northern Red-backed Vole Myodes rutilus French: Campagnol boréal / German: Polarrételmaus / Spanish: Topillo rojo septentrional Other common names: Red ole Taxonomy. Mus rutilus Pallas, 1779, center of Ob River delta, Siberia, Russia. In the past, M. rutilus was included in Evotomys or Clethrionomys; both generic names are junior synonyms of Mpyodes. Present and past hybridization was documented in zone of sympatry with M. glareolus and in parapatric zone with M. gapperi. A number of subspecies have been recognized on both sides of Beringia, and their validity has been questioned with traditional subspecific systematics. Molecular reconstructions retrieved three divergent allopatric lineages with zones of secondary contact between them. These lineages diverged more than 100,000 years ago. Beringian lineage encompasses all populations in North America, Kamchatka, Sakhalin, and Hokkaido. Remaining Palearctic populations are in two lineages, separated by the Yenisei River. Monotypic. Distribution. From N ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on pages 303-304, DOI: 10.5281/zenodo.6707142 ...